2021
DOI: 10.7150/jca.53242
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood biomarkers predict immune-related adverse events in non-small cell lung cancer patients treated with pembrolizumab: a multicenter retrospective study

Abstract: Background: Pembrolizumab is currently the standard treatment for patients with advanced non-small cell lung cancer (NSCLC). However, the association between immune-related adverse events (irAEs) and peripheral blood cell counts remains unclear. We aimed at identifying peripheral blood cell counts that may predict the development of pembrolizumab-induced irAEs. Methods: We retrospectively analyzed data on consecutive patients with advanced NSCLC who received pembrolizumab monotherapy as first-line or later-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
0
32
1
Order By: Relevance
“…Egami et al reported that markers, such as NLR, PLR, absolute lymphocyte count, and lymphocyte-to-monocyte ratio, were useful predictors associated with the development of irAEs by setting an optimal cutoff value using the receiver operating characteristic curve. 11 Optimal cutoff values for these markers vary depending on the target patient population and should be interpreted with caution.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Egami et al reported that markers, such as NLR, PLR, absolute lymphocyte count, and lymphocyte-to-monocyte ratio, were useful predictors associated with the development of irAEs by setting an optimal cutoff value using the receiver operating characteristic curve. 11 Optimal cutoff values for these markers vary depending on the target patient population and should be interpreted with caution.…”
Section: Dovepressmentioning
confidence: 99%
“…Egami et al reported that pretreatment NLR > 2.3 and PLR > 165 were significantly correlated with an increasing incidence of irAEs in NSCLC patients who received pembrolizumab monotherapy. 11 Another retrospective study reported that elevated body mass index, higher number of pembrolizumab cycles, and derived NLR < 3 were correlated with an increased incidence of irAEs in patients receiving pembrolizumab for various cancers, such as lung cancer, melanoma, lymphoma, gastric cancer, and urothelial cancer. 12 Although these studies have reported on predictive factors correlated with the development of irAEs in clinical practice, patients in these studies only received pembrolizumab; other ICIs have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This single-center, retrospective observational study was carried out at the National Cancer Center Hospital, a high-volume cancer center in Tokyo, Japan, using data retrieved from electronic medical records. The methodology adopted in this observational study adhered to the STROBE Statement (23) and was the same as that followed in previous studies conducted by our coauthors (24)(25)(26).…”
Section: Patientsmentioning
confidence: 99%
“…It was verified that mOS in NLR ≥ 3.06 group was shorter than in NLR<3.06 group (2.7m vs 8.6m P=0.000). Higher NLR was significantly associated with an increased risk of immune-related adverse events (irAE) [24]. In our research, the NLR values of patients who experienced immune-related encephalitis and cardiotoxicity were 12.5 and 10.7 respectively, obviously higher than the cutoff value.…”
Section: Discussionmentioning
confidence: 61%